The Effects of Crude Oil Price Changes on the Indonesian Stock Market: A Sector Investigation - Rahmanto, Fariz; Riga, Muhammad Hira; Indriana, Vika (The Indonesian Capital Market Review, 2016)
This article contributes to country specific result on the responses of sector stock indices to crude oil price changes. Using linear and asymmetric models and by studying the association of crude oil and stock price, this article aims to explain about the short-term responses of Indonesian sector stock indices to crude oil price changes. Besides, we also try to figure out whether there are asymmetric responses within. Our findings suggest that the strength and the sensitivity of this association vary across sectors, and the effects are positive for all sectors. We also find strong significance of asymmetry reactions for Agriculture and Consumer Goods sector stock returns due to changes in crude oil price